2015
DOI: 10.1016/j.cmet.2015.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Browning of Subcutaneous White Adipose Tissue in Humans after Severe Adrenergic Stress

Abstract: Since the presence of brown adipose tissue (BAT) was confirmed in adult humans, BAT has become a therapeutic target for obesity and insulin resistance. We examined whether human subcutaneous white adipose tissue (sWAT) can adopt a BAT-like phenotype using a clinical model of prolonged and severe adrenergic stress. sWAT samples were collected from severely burned and healthy individuals. A subset of burn victims were prospectively followed during their acute hospitalization. Browning of sWAT was determined by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
297
5
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(320 citation statements)
references
References 31 publications
15
297
5
3
Order By: Relevance
“…In line with our results, the promotion of BAT activity or the browning of WAT has been reported to result in increased energy expenditure and protection against obesity and type 2 diabetes (35,36,52,53). These preclinical observations together with the recent discovery that browning of scWAT occurs in adult humans make this cell type an attractive therapeutic target for the treatment of obesity and type 2 diabetes (35,53,54). Our results suggest that molecules arising from the ALOX5/ALOX5AP pathway may have potential therapeutic effects.…”
Section: Discussionsupporting
confidence: 90%
“…In line with our results, the promotion of BAT activity or the browning of WAT has been reported to result in increased energy expenditure and protection against obesity and type 2 diabetes (35,36,52,53). These preclinical observations together with the recent discovery that browning of scWAT occurs in adult humans make this cell type an attractive therapeutic target for the treatment of obesity and type 2 diabetes (35,53,54). Our results suggest that molecules arising from the ALOX5/ALOX5AP pathway may have potential therapeutic effects.…”
Section: Discussionsupporting
confidence: 90%
“…Contrary to mice, in humans gene expression related to browning is more prevalent in visceral than in subcutaneous WAT [95], but whether chronic exposure to low temperature promotes browning of visceral tissue is still not known. These results were confirmed by Sidossis et al [84] who showed that in patients exposed to a prolonged adrenergic stress, such as burn trauma, subcutaneous WAT contains multilocular UCP1-positive adipocytes with increased mitochondrial density and respiratory capacity.…”
Section: Browning Of Wat As a Possible Aid To Fight Metabolic Diseasessupporting
confidence: 66%
“…Although the BAT contribution to human energy expenditure (TEE) is minor, browning has been proposed as a new possible target to fight obesity and improve whole body metabolism and TEE [5], [19], [84].…”
Section: Browning Of Wat As a Possible Aid To Fight Metabolic Diseasesmentioning
confidence: 99%
“…In animals, prolonged cold stimulation also induces browning of distinct white adipose tissue (WAT) depots, likely contributing to improved substrate metabolism (7). This phenomenon also has recently been observed in human subcutaneous WAT upon severe and prolonged adrenergic stress (8).…”
Section: Short-term Cold Acclimation Recruits Brown Adipose Tissue Inmentioning
confidence: 82%
“…It is likely that a greater or more prolonged adrenergic stimulus is required to induce browning within these white adipose depots. Sidossis et al (8) recently showed that upon severe and prolonged adrenergic stress (i.e., in burn victims), browning of subcutaneous WAT became apparent, which was associated with increased wholebody EE.…”
Section: Discussionmentioning
confidence: 99%